2014
DOI: 10.1155/2014/580418
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Florfenicol and Diclazuril in Compound Powder by RP-HPLC-UV Method

Abstract: A RP-HPLC-UV method was developed and validated for simultaneous determination of florfenicol and diclazuril in compound powder. The separation involved using a SinoChoom ODS-BP C 18 (5 m, 4.6 mm × 250 mm) analytical column. The mobile phase was a mixture of acetonitrile-0.2% phosphoric acid (pH was adjusted to 3.0 with triethylamine). The ratio of acetonitrile and 0.2% phosphoric acid in the mobile phase was 60 : 40 (v/v) from 0 minutes to 6 minutes and 70 : 30 (v/v) from 6.1 minutes to 15 minutes. The flow r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…Previous studies demonstrated different methods for quantification of FLR either alone or in combination with other drugs, including spectrophotometry [6][7][8], high-performance liquid chromatography (HPLC) [9][10][11][12][13][14][15][16], voltammetry [17] and gas chromatography (GC) [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated different methods for quantification of FLR either alone or in combination with other drugs, including spectrophotometry [6][7][8], high-performance liquid chromatography (HPLC) [9][10][11][12][13][14][15][16], voltammetry [17] and gas chromatography (GC) [18,19].…”
Section: Introductionmentioning
confidence: 99%